Implementación de un sistema de control interno para la fundación Asof, ubicada en la provincia de Cotopaxi cantón Latacunga - Paste Guanoluisa, Daysi Magaly (2016)
The Solidary and Family support Foundation (ASOF) is an organization that has been dedicated to the provision of microcredit to women with limited economic resources, or who are seeking to develop entrepreneurial projects in communities, within the "ASOF" foundation, main problem that was identified is; the lack of assignment of duties to staff working in this organization also breach of organizational objectives proposed by "ASOF". In carrying out the research work the theoretical and research background on administrative management, internal control and evaluation thereof were analyzed….